Structural characterization of μc-Si:H films produced by R.F. magnetron sputtering - Cerqueira, M. F. (1998)
Microcrystalline silicon thin films were produced by R.F. magnetron sputtering. The microstructure of these films has been studied by X-ray diffraction, transmission electron microscopy (TEM) and Raman spectroscopy. Average values of crystalline size and strain obtained by the different tecnhiques used are critically compared and the reasons for the differences are discussed.